Niobium-doped nickel-cobalt-manganese lithium aluminate quaternary material, preparation method thereof and lithium ion battery using niobium-doped nickel-cobalt-manganese lithium aluminate quaternary material

By doping niobium into the nickel-cobalt-manganese-aluminate quaternary material and adopting a specific preparation method, the problem of structural phase change in the material during charging and discharging is solved, and the cycle stability of the material and the battery life are improved.

CN119905501APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311416457.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The quaternary material of nickel-cobalt manganese aluminate is prone to structural phase change during charging and discharging, resulting in microcracking, powdering and damage to the electrode structure, which in turn leads to the failure of lithium-ion batteries.

Method used

By doping niobium into a nickel-cobalt manganese lithium aluminate quaternary material and adopting a specific preparation method, including reacting a nickel-cobalt manganese ternary precursor and a niobium-containing compound using an aluminum-based hydrotalcite suspension, followed by ball milling and heat treatment with a lithium source, a niobium-doped quaternary material with a core-shell structure is prepared.

Benefits of technology

The uniform distribution of niobium elements and the concentration of particle size distribution are achieved, the circulation stability of the material is improved, the structural damage during charging and discharging is reduced, and the service life of lithium-ion batteries is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905501A_ABST
    Figure CN119905501A_ABST
Patent Text Reader

Abstract

The invention relates to a niobium-doped nickel-cobalt-manganese lithium aluminate quaternary material, a preparation method thereof and a lithium ion battery using the niobium-doped nickel-cobalt-manganese lithium aluminate quaternary material. The method comprises the following steps: (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound, and reacting to obtain a pre-product; (2) carrying out ball milling on the pre-product and a lithium-containing compound, and carrying out heat treatment on the obtained mixture in an oxygen-containing atmosphere; wherein the aluminum-based hydrotalcite contains a transition metal element, the transition metal element is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5): 1; the niobium-doped lithium nickel cobalt manganese aluminate quaternary material prepared by the method disclosed by the invention has a core-shell structure, the niobium element is uniformly doped, the particle size distribution is relatively concentrated, and a lithium ion battery prepared by taking the niobium-doped lithium nickel cobalt manganese aluminate quaternary material as a positive electrode material has relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of positive electrode materials for lithium-ion batteries, and in particular to a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material, a preparation method thereof, and a lithium-ion battery using the same. Background Art

[0002] Lithium Nickel Cobalt Manganese Aluminum Oxide LiNi 1-x-y-z Co x Mn y Al z As a quaternary positive electrode material, O2(NCMA) combines some advantages of NCM and NCA materials, and has the advantages of high specific capacity and good safety performance. However, when 1-xyz≥0.6, the battery is in the high voltage range (4.1-4.3V (vs.Li) during the charge and discharge process. + / Li)), nickel-cobalt-manganese-aluminum-lithium quaternary material will Structural phase change, after long-term and multiple cycles, microcracks appear in the material particles until the particles are pulverized, and the adverse side reactions with the electrolyte increase, the electrode structure is destroyed, and finally the battery fails. Starting from the crystal structure and material morphology is an effective way to improve the structural stability of high-nickel layered multi-element materials.

[0003] From the perspective of crystal structure, the introduction of niobium into nickel-cobalt-manganese-aluminum quaternary materials can improve the stability of positive electrode materials, expand the lithium ion insertion / extraction channels and reduce the degree of cation mixing, thereby improving material performance. The conventional niobium doping method is to directly mix niobium compounds such as niobium oxide with the quaternary precursor, and then add a lithium source for lithium calcination. 5+ Due to the large ion radius, niobium elements are usually difficult to diffuse evenly into the quaternary material structure to achieve the ideal doping effect.

[0004] From the perspective of material morphology, "core-shell" or "gradient" secondary spherical particles are usually constructed with high nickel and low manganese in the inner core and low nickel and high manganese in the outer layer. Some also require the primary particles to be arranged in a "radial" structure from the center of the spherical particle to the surface of the spherical particle. This kind of multi-layered material can alleviate the side reactions between the surface high nickel components and the electrolyte to a certain extent, reduce the intercrystalline stress caused by volume deformation during charging and discharging, reduce microcracks, and improve cycle performance. However, it is very difficult to synthesize precursors with a "radial" structure from the center of the spherical particle to the surface of the particle. On the other hand, the synthesis efficiency of "core-shell" or "gradient" quaternary materials distinguished by transition metal concentration is low and difficult, and they are not suitable for large-scale production. Summary of the invention

[0005] The purpose of the present disclosure is to provide a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material, a preparation method thereof, and a lithium-ion battery using the same. The niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method of the present disclosure has a core-shell structure, and the niobium element is evenly distributed and the particle size distribution is concentrated. When used as a positive electrode material for a lithium-ion battery, good cycle stability can be obtained.

[0006] In order to achieve the above-mentioned object, the present disclosure provides, in a first aspect, a method for preparing a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material, the method comprising the following steps:

[0007] (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to react and obtain a pre-product;

[0008] (2) ball milling the pre-product and the lithium-containing compound, and heat treating the obtained mixture in an oxygen-containing atmosphere;

[0009] The aluminum-based hydrotalcite contains a transition metal element, the transition metal element is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1;

[0010] The method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps:

[0011] S01. Adding a reaction base liquid to a primary reactor, wherein the reaction base liquid comprises water, an alkaline solution and an ammonia complexing liquid, and the amount of the reaction base liquid added is 30%-80% of the effective volume of the primary reactor;

[0012] S02. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the primary reactor, and when the primary reactor is full, the material in the primary reactor is concentrated, and the concentrated solution is refluxed into the primary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 3-4 times the effective volume of the primary reactor, and the material in the primary reactor is transferred to the secondary reactor;

[0013] S03. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the secondary reactor, and when the secondary reactor is full, the material in the secondary reactor is concentrated, and the concentrated solution is refluxed into the secondary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 2-3 times the effective volume of the secondary reactor, and the material in the secondary reactor is transferred into the tertiary reactor;

[0014] S04. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, the alkaline solution and the ammonia complex solution are continuously introduced into the tertiary reactor, and when the tertiary reactor is full, the material in the tertiary reactor is concentrated, and the concentrated solution is refluxed into the tertiary reactor until the D50 particle size of the particles in the tertiary reactor is 9-11 μm;

[0015] In step S01, when adding the reaction base solution, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-5 g / L;

[0016] In step S02, before the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.2-11.3 and the NH3 concentration is 3.5-4.5 g / L; after the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 10.7-11.0 and the NH3 concentration is 3-4 g / L;

[0017] In step S03, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the secondary reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L;

[0018] In step S04, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the three-stage reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L.

[0019] Optionally, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2, where 0 <a≤0.1,0<b≤0.1。

[0020] Optionally, in step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite to the niobium element in the niobium-containing compound is greater than 2:1.

[0021] Optionally, the niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate;

[0022] The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate;

[0023] Optionally, the average particle size of the niobium-containing compound is 50-80 nm, and the average particle size of the lithium-containing compound is 6-8 μm.

[0024] Optionally, the molar ratio of the total molar sum of nickel, cobalt, manganese, aluminum and niobium in the pre-product to the lithium in the lithium-containing compound is 1:(1.0-1.1).

[0025] Optionally, in step (2), the heat treatment comprises the following steps:

[0026] a. Raise the temperature to 300-400°C at a heating rate of 1-8°C / min for the first calcination for 1-3h;

[0027] b. Continue heating to 450-500°C at a heating rate of 1-8°C / min and perform a second calcination for 1-3h;

[0028] c. Continue heating to 700-800°C at a heating rate of 2-6°C / min for the third calcination for 10-15h;

[0029] d. Cool down to 300-400°C at a cooling rate of 1-3°C / min, and then cool to below 100°C;

[0030] The oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere.

[0031] Optionally, the ball milling time is 1-4h.

[0032] Optionally, the mixed salt solution contains nickel ions, cobalt ions and manganese ions, and the total molar concentration of the nickel ions, the cobalt ions and the manganese ions is 1.8-2.5 mol / L.

[0033] Optionally, the alkaline solution comprises a sodium hydroxide solution and / or a potassium hydroxide solution, wherein OH - The concentration is 5-10 mol / L;

[0034] The ammonia complex solution includes aqueous ammonia, and the mass fraction of NH3 in the ammonia complex solution is 15-22%.

[0035] Optionally, in the primary reactor, the secondary reactor and the tertiary reactor, the reaction temperature is 50-65° C., the stirring speed is 100-400 rpm, and the oxygen content is less than 0.01% by volume.

[0036] Optionally, the effective volume of the secondary reactor is 3-4 times the effective volume of the primary reactor, and the effective volume of the tertiary reactor is 3-4 times the effective volume of the secondary reactor.

[0037] A second aspect of the present disclosure provides a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method described in the first aspect of the present disclosure.

[0038] Optionally, the quaternary material is a particle comprising a core and a shell layer coated outside the core;

[0039] The diameter distance of the particles is less than 0.68.

[0040] Optionally, A Nb With D Nb The ratio is 0.9-1.1;

[0041] Based on the total molar amount of nickel, cobalt, manganese, aluminum and niobium on the surface of the particles, A Nb represents the molar percentage of niobium element on the surface of the particle;

[0042] Based on the total molar mass of nickel, cobalt, manganese, aluminum and niobium in the bulk phase of the particles, D Nb represents the molar ratio of niobium element in the bulk phase of the particles.

[0043] Optionally, the quaternary material includes a chemical formula of LiNi 1-x-y-z-n Co x Mn y Al z Nb n Particles of O2, 0<x<0.2, 0<y<0.1, 0<z<0.05, 0.002<n<0.02.

[0044] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material as described in the second aspect of the present disclosure.

[0045] Through the above technical scheme, the present disclosure adopts a nickel-cobalt-aluminum ternary precursor prepared by a specific method to react with an aluminum-based hydrotalcite suspension containing transition metal elements and a niobium-containing compound, and then mixes with a lithium source and roasts to obtain a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material. The above quaternary material has a core-shell structure and a complete crystal structure, which relieves the intercrystalline stress caused by volume deformation during charging and discharging; the microcracks caused by multiple cyclic phase changes are also less, further improving the cycle performance of the battery; and the method disclosed in the present disclosure can reduce the difficulty of synthesizing the niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material, improve the doping effect of the niobium element, and the niobium element in the prepared quaternary material is evenly distributed, with a small diameter distance and a relatively concentrated particle size distribution. Using it as a positive electrode material for a lithium-ion battery can further improve the cycle performance of the material.

[0046] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0048] Figure 1 is a scanning electron microscope image of the quaternary material A1 prepared in Example 1 of the present disclosure;

[0049] Figure 2 It is a scanning electron microscope image of the quaternary material D6 prepared in comparative example 6 of the present disclosure. DETAILED DESCRIPTION

[0050] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0051] The first aspect of the present disclosure provides a method for preparing a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material, the method comprising the following steps:

[0052] (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to react and obtain a pre-product;

[0053] (2) ball milling the pre-product and the lithium-containing compound, and heat treating the obtained mixture in an oxygen-containing atmosphere;

[0054] The aluminum-based hydrotalcite contains a transition metal element, the transition metal element is cobalt or nickel, and the molar ratio of the transition metal element to the aluminum element is (2-5):1;

[0055] The method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps:

[0056] S01. Adding a reaction base liquid to a primary reactor, wherein the reaction base liquid comprises water, an alkaline solution and an ammonia complexing liquid, and the amount of the reaction base liquid added is 30%-80% of the effective volume of the primary reactor;

[0057] S02. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the primary reactor, and when the primary reactor is full, the material in the primary reactor is concentrated, and the concentrated solution is refluxed into the primary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 3-4 times the effective volume of the primary reactor, and the material in the primary reactor is transferred to the secondary reactor;

[0058] S03. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the secondary reactor, and when the secondary reactor is full, the material in the secondary reactor is concentrated, and the concentrated solution is refluxed into the secondary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 2-3 times the effective volume of the secondary reactor, and the material in the secondary reactor is transferred into the tertiary reactor;

[0059] S04. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, the alkaline solution and the ammonia complex solution are continuously introduced into the tertiary reactor, and when the tertiary reactor is full, the material in the tertiary reactor is concentrated, and the concentrated solution is refluxed into the tertiary reactor until the D50 particle size of the particles in the tertiary reactor is 9-11 μm;

[0060] In step S01, when adding the reaction base solution, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-5 g / L;

[0061] In step S02, before the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.2-11.3 and the NH3 concentration is 3.5-4.5 g / L; after the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 10.7-11.0 and the NH3 concentration is 3-4 g / L;

[0062] In step S03, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the secondary reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L;

[0063] In step S04, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the three-stage reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L.

[0064] In the present disclosure, the reaction of the suspension containing aluminum-based hydrotalcite with the nickel-cobalt-manganese ternary precursor and the niobium-containing compound in step (1) belongs to liquid phase coating, which has a better coating effect than the dry ball milling using hydrotalcite nanosheets directly, and the particle size distribution of the prepared quaternary material is more concentrated, and has better electrochemical performance, especially cycle stability; during the heat treatment process, the cobalt element or nickel element in the aluminum-based hydrotalcite can drive the niobium element into the material through the "cooperative diffusion effect", reducing the difficulty of synthesizing the quaternary material. And the strong chemical bond of Nb-O can be used to inhibit the structural distortion and structural collapse of the material during the charge and discharge process; and the particle size distribution of the quaternary material prepared by the method of the present disclosure is relatively concentrated, which can further improve the cycle stability of the material.

[0065] In the present disclosure, the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere, preferably an oxygen atmosphere, wherein the definitions of the oxygen-containing atmosphere and the air atmosphere are conventional in the art.

[0066] According to one embodiment of the present disclosure, in step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite to the niobium element in the niobium-containing compound is greater than 2:1. Meeting the above ratio can reduce the content of niobium element on the surface, so that the prepared material has better electrochemical properties.

[0067] According to one embodiment of the present disclosure, the niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate. When the niobium-containing compound includes more than two kinds, their proportion is not limited. The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate. When the lithium-containing compound includes more than two kinds, their proportion is not limited.

[0068] According to one embodiment of the present disclosure, the average particle size of the niobium-containing compound is 50-80 nm, preferably 50-60 nm; the average particle size of the lithium-containing compound is 6-8 μm, preferably 6-7 μm.

[0069] According to one embodiment of the present disclosure, the molar ratio of the total molar sum of nickel, cobalt, manganese, aluminum and niobium in the pre-product to the lithium in the lithium-containing compound is 1:(1.0-1.1), preferably 1:(1.02-1.08).

[0070] In the present disclosure, in step (1), the feed amounts of aluminum-based hydrotalcite, nickel-cobalt-manganese ternary precursor and niobium-containing compound are LiNi 1-x-y-z-n Co x Mn y Al z Nb nThe molar ratio of Ni, Co, Mn, Al and Nb in the O2 material can be weighed to meet the molar content of Ni, Co, Mn, Al and Nb in the final product.

[0071] According to one embodiment of the present disclosure, in step (2), the heat treatment comprises the following steps:

[0072] In step (2), the heat treatment comprises the following steps:

[0073] a. Raise the temperature to 300-400°C at a heating rate of 1-8°C / min for the first calcination for 1-3h;

[0074] b. Continue heating to 450-500°C at a heating rate of 1-8°C / min and perform a second calcination for 1-3h;

[0075] c. Continue heating to 700-800°C at a heating rate of 2-6°C / min for the third calcination for 10-15h;

[0076] d. Cooling to 300-400°C at a cooling rate of 1-3°C / min, and then cooling to below 100°C. The cooling method may be furnace cooling, for example;

[0077] The above heat treatment method can make the pre-product and the lithium-containing compound fully decompose into oxides in the first and second calcination stages, improve the solid phase reaction efficiency in the third calcination stage, and generate a quaternary material with a more complete crystal form and a more concentrated particle size distribution. After the calcination, the stress between the grains is at least partially eliminated through annealing treatment, thereby improving the cycle stability of the quaternary material.

[0078] In the present disclosure, the ball milling method of step (2) is solid phase ball milling. Furthermore, the ball milling time is 1-4 hours. Meeting the above ball milling time can ensure sufficient coating of the lithium-containing compound and avoid the precursor particles from being broken due to too long ball milling time.

[0079] According to one embodiment of the present disclosure, a method for preparing a suspension containing aluminum-based hydrotalcite comprises the following steps:

[0080] A. preparing a first solution comprising a transition metal source and an aluminum source;

[0081] B. Add the first solution and the alkaline solution into a colloid mill at a rotation speed of 1000-3000 r / min for 2-5 min to obtain a suspension.

[0082] In the present disclosure, the transition metal source can be, for example, a soluble salt of a transition metal, preferably including one or more of nickel sulfate, nickel chloride, nickel nitrate and nickel acetate; or, the soluble transition metal salt includes one or more of cobalt sulfate, cobalt chloride, cobalt nitrate and cobalt acetate; when the transition metal source includes more than two types, there is no specific limitation on their ratio.

[0083] In the present disclosure, the aluminum source includes one or more of aluminum sulfate, aluminum chloride, aluminum nitrate and aluminum acetate; when the aluminum source includes two or more, the ratio thereof is not specifically limited.

[0084] In the present disclosure, the alkaline solution comprises a soluble alkali and a soluble alkaline salt, wherein the soluble alkali comprises sodium hydroxide and / or potassium hydroxide; the soluble alkaline salt comprises sodium carbonate and / or potassium carbonate; specifically, the soluble alkali may be sodium hydroxide, and the soluble alkaline salt may be sodium carbonate. Further, the concentration of the soluble alkali is 1-2 mol / L, and the concentration of the soluble alkaline salt is 0.25-0.75 mol / L.

[0085] In the present disclosure, the volume ratio of the first solution to the alkaline solution is (0.8-1.5):1; for example, they can be mixed in equal volumes.

[0086] In the present disclosure, the molar ratio of the transition metal source calculated as transition metal element to the aluminum source calculated as aluminum element is (2-5):1; the total molar concentration of the transition metal source calculated as transition metal element and the aluminum source calculated as aluminum element is 0.5-1.25 mol / L.

[0087] According to one embodiment of the present disclosure, step (1) comprises: mixing a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound, and then aging the mixture in a water bath at 95-98°C for 2-4 hours, performing solid-liquid separation on the aging mixture, and washing the obtained solid until the pH value of the washing liquid is below 7.5; then drying the washed solid at 80-120°C for 8-12 hours to obtain a pre-product; wherein the solid-liquid separation method is conventional in the art, such as filtration; and the drying method is conventional in the art.

[0088] In the present disclosure, pH values ​​are all tested values ​​under 25°C and normal pressure conditions.

[0089] According to one embodiment of the present disclosure, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2, where 0 <a≤0.1,0<b≤0.1。

[0090] According to one embodiment of the present disclosure, the D50 particle size of the nickel-cobalt-manganese ternary precursor is 9-11 μm, preferably 9.5-10.5 μm.

[0091] In the present disclosure, the mixed salt solution can be selected within a certain range, for example, the mixed salt solution contains nickel ions, cobalt ions and manganese ions; the total molar concentration of nickel ions, cobalt ions and manganese ions can be 1.8-2.5 mol / L; the molar ratio of nickel ions, cobalt ions and manganese ions in the mixed salt solution can be, for example, the same as the molar ratio of nickel element, cobalt element and manganese element in the nickel-cobalt-manganese ternary precursor.

[0092] In the present disclosure, specifically, the mixed salt solution can be obtained by dissolving a soluble nickel salt, a soluble cobalt salt and a soluble manganese salt in deionized water.

[0093] According to the present disclosure, the alkaline solution and the ammonia complex solution can be selected within a certain range. For example, the alkaline solution may include a sodium hydroxide solution and / or a potassium hydroxide solution. - The concentration may be 5-10 mol / L; the ammonia complex solution may include aqueous ammonia, and the mass fraction of NH3 in the ammonia complex solution may be 15-22%.

[0094] According to the present disclosure, the reaction conditions in each stage of the reactor can vary within a certain range. For example, in the first stage reactor, the second stage reactor and the third stage reactor, the reaction temperature can be 50-65°C, the stirring speed can be 100-400 rpm, and the oxygen content can be less than 0.01% by volume.

[0095] According to the present disclosure, in order to further control the speed and progress of crystal nucleation or growth in each stage of the reactor, preferably, the effective volume of the secondary reactor can be 3-4 times the effective volume of the primary reactor, and the effective volume of the tertiary reactor can be 3-4 times the effective volume of the secondary reactor.

[0096] According to one embodiment of the present disclosure, the method further includes:

[0097] S05. Separating the particles having a particle size of 9-11 μm at D50 in the three-stage reactor, and then washing the particles;

[0098] Specifically, the particles are sent to a washing machine and washed with deionized water, alkaline solution and deionized water in sequence until the pH value of the washing liquid is ≤8.0; the washed particles are dried at 100-150°C for 5-12h to obtain a nickel-cobalt-manganese ternary precursor; the alkaline solution can be, for example, a sodium hydroxide solution with a mass fraction of 1-2%.

[0099] A second aspect of the present disclosure provides a niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method described in the first aspect of the present disclosure.

[0100] According to one embodiment of the present disclosure, the quaternary material is a particle including a core and a shell layer coated outside the core.

[0101] The quaternary material disclosed in the present invention has a core-shell structure, wherein the core is formed by the agglomeration of primary particles, and the shell is formed by the arrangement of primary particles and has a "radial" structure, with a small diameter distance and a concentrated particle size distribution, which makes it easier to react with oxygen during the solid-phase reaction, and the resulting crystal structure is more complete, which alleviates the intercrystalline stress caused by volume deformation during the charge and discharge process; there are also fewer microcracks caused by multiple cyclic phase changes, which further improves the cycle performance of the battery.

[0102] According to one embodiment of the present disclosure, the particle size of the inner core is 2-4 μm, and the thickness of the shell is 1-6 μm.

[0103] According to one embodiment of the present disclosure, the diameter distance of the particles is less than 0.68, and the quaternary material having the above diameter distance can further improve the cycle stability of the battery.

[0104] According to one embodiment of the present disclosure, the D50 particle size of the particles is 9-11 μm.

[0105] In the present disclosure, particles may have a spherical and / or spheroidal morphology, and the definitions of "spherical" and "spheroidal" are conventional in the art.

[0106] According to one embodiment of the present disclosure, A Nb With D Nb The ratio is 0.9-1.1, preferably 0.95-1.05; based on the total molar amount of nickel, cobalt, manganese, aluminum and niobium on the surface of the particles, A Nb represents the molar ratio of the niobium element on the surface of the particle; based on the total molar ratio of the nickel element, cobalt element, manganese element, aluminum element and niobium element in the bulk phase of the particle, D Nb It represents the molar proportion of niobium element in the bulk phase of the particles; the niobium element of the material within the above range is distributed in the bulk phase, which further optimizes the crystal structure of the material, and can effectively remove residual alkali on the surface, thereby improving long-term cycle performance.

[0107] In the present disclosure, "the molar fraction of niobium element on the surface of the particle" refers to the ratio of the molar number of niobium element on the surface of the particle to the total molar number of nickel element, cobalt element, manganese element, aluminum element and niobium element on the surface; "the molar fraction of niobium element in the bulk phase of the particle" refers to the ratio of the molar number of niobium element in the bulk phase of the particle to the total molar number of nickel element, cobalt element, manganese element, aluminum element and niobium element in the bulk phase.

[0108] According to one embodiment of the present disclosure, the core and shell of the particle may have the same chemical composition.

[0109] According to one embodiment of the present disclosure, the quaternary material includes a chemical formula of LiNi 1-x-y-z- n Co x Mn y Al z Nb n Particles of O2, 0<x<0.2, 0<y<0.1, 0<z<0.05, 0.002<n<0.02.

[0110] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material as described in the first aspect of the present disclosure.

[0111] Furthermore, the negative electrode material of the lithium ion battery may be, for example, a lithium sheet, and the electrolyte may be, for example, an alkyl carbonate solution of LiPF6. This is conventional in the art and no specific requirements are made here.

[0112] The present disclosure is further described below by way of examples, but the present disclosure is not limited thereto. The raw materials, reagents, instruments and equipment designed in the examples of the present disclosure can all be purchased unless otherwise specified.

[0113] The test method involved in the embodiments of the present disclosure is as follows:

[0114] (1) Test method and conditions of scanning electron microscope: FEIQuanta 200FEG, rated voltage of the equipment is 10 kV.

[0115] (2) The particle size and diameter distance were measured using the Mastersizer 2000 laser particle size analyzer from Malvern, UK.

[0116] (3) The element analysis of the particle surface was carried out using the ESCALab220i-XL X-ray photoelectron spectrometer from VG Scientific.

[0117] (4) The bulk element analysis of the particles was carried out using a Perkin-Elmer Optima 3300DV inductively coupled plasma (ICP) element analyzer.

[0118] (5) Chemical formula testing method: obtained based on the results of bulk element analysis.

[0119] Example 1

[0120] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material A1 was prepared by the following steps:

[0121] (1) Preparation of nickel-cobalt-aluminum ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 (referred to as NCM811):

[0122] a. According to the molar ratio of Ni:Co:Mn=8:1:1, nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate were dissolved in deionized water to prepare a mixed salt solution with a total molar concentration of metal ions of 2.0 mol / L; sodium hydroxide was dissolved in deionized water to prepare OH - An alkaline solution with a molar concentration of 6 mol / L; an ammonia solution with a NH3 mass fraction of 22% is prepared as an ammonia complexing solution;

[0123] b. Add deionized water accounting for 50% of the effective volume of the primary reactor, and then add the alkaline solution and ammonia complex solution prepared in step a as the reaction base solution, so that the NH3 concentration in the primary reactor is 4 g / L and the pH value is 11.3;

[0124] c. Under a nitrogen atmosphere and a stirring condition of 400 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the primary reactor in step b. When the primary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the primary reactor, and the clear liquid is discharged into the waste liquid tank. When the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is 4 times the effective volume of the primary reactor, the feeding is stopped, and the materials in the primary reactor are transferred to the secondary reactor;

[0125] The effective volume of the secondary reactor is 4 times that of the primary reactor. The reaction temperature in the primary reactor is 60°C. Before the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 11.3 and the NH3 concentration at 4g / L. After the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 10.8 and the NH3 concentration at 3.5g / L.

[0126] d. Under a nitrogen atmosphere and a stirring condition of 300 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the secondary reactor in step c. When the secondary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the secondary reactor, and the clear liquid is discharged into the waste liquid tank. When the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is 3 times the effective volume of the secondary reactor, the feeding is stopped, and the materials in the secondary reactor are transferred to the tertiary reactor;

[0127] The effective volume of the tertiary reactor is three times that of the secondary reactor. The reaction temperature in the secondary reactor is 60°C. The flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the secondary reactor at 10.8 and the NH3 concentration at 3g / L.

[0128] e. Under a nitrogen atmosphere and a stirring condition of 200 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the tertiary reactor in step d. When the tertiary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the tertiary reactor, and the clear solution is discharged into the waste liquid tank. When the D50 particle size of the particles in the tertiary reactor reaches 9 μm, the feeding is stopped;

[0129] The reaction temperature in the third-stage reactor was 60°C, and the flow rates of the alkaline solution and the ammonia complex solution were controlled to maintain the pH value in the third-stage reactor at 10.8 and the NH3 concentration at 3 g / L;

[0130] The oxygen content in the first-stage reactor, the second-stage reactor and the third-stage reactor is less than 0.01% by volume;

[0131] f. After the feeding is stopped in step e, the materials in the three-stage reactor are sequentially washed with water, alkali washed, and washed with water until the pH of the washing solution is ≤8.0, wherein the alkali solution used for alkali washing is a sodium hydroxide solution with a mass percentage concentration of 1%, and the alkali washing time is 2h;

[0132] g. Put the washed material in step f into an oven, dry it at 100° C. for 12 h, and then pass it through a 200-mesh sieve to obtain a ternary precursor of lithium nickel cobalt manganese oxide (Ni 0.8 Co 0.1 Mn 0.1 (OH)2).

[0133] (2) dissolving cobalt sulfate calculated as Co element and aluminum sulfate calculated as Al element in a molar ratio of 3:1 in deionized water to prepare a first solution with a total metal ion concentration of 1.0 mol / L;

[0134] Prepare an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L;

[0135] The first solution and the alkaline solution were added into a colloid mill at a volume ratio of 1:1 and mixed for 3 minutes at a speed of 3000 r / min to obtain cobalt aluminum hydrotalcite Co6Al2(OH) 16 CO3·6H2O suspension;

[0136] The NCM811 precursor, the suspension containing cobalt aluminum hydrotalcite (in terms of solid phase), and nano niobium pentoxide (average particle size of 50 nm) were weighed and mixed in a molar ratio of 100:1:0.5, stirred and aged in a 98°C water bath for 3 hours, then washed and filtered repeatedly until the pH of the filtrate was below 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain a pre-product;

[0137] (3) The above pre-product and micro powder lithium hydroxide (average particle size of 7 μm) were weighed and mixed for 2.5 h according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.06, and then the temperature was raised to 350°C at a temperature rate of 2°C / min in an oxygen atmosphere, and the mixture was calcined at a constant temperature for 3 h. The temperature was then raised to 480°C at a temperature rate of 2°C / min, and the mixture was calcined at a constant temperature for 3 h. The temperature was then raised to 750°C at a temperature rate of 4°C / min, and the mixture was calcined at a constant temperature for 15 h. Finally, the temperature was lowered to 350°C at a temperature rate of 2°C / min, and the mixture was then cooled to room temperature in the furnace to obtain niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material A1, whose chemical formula is LiNi 0.734 Co 0.147 Mn 0.092 Al 0.01 8Nb 0.009 O2, parameters are listed in Table 1;

[0138] The quaternary material A1 was tested by scanning electron microscope, and the results are as follows Figure 1 shown.

[0139] Example 2

[0140] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material A2 was prepared by the following method:

[0141] (1) Preparation of nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 (referred to as NCM9055):

[0142] a. According to the molar ratio of Ni:Co:Mn=9:0.5:0.5, nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate were dissolved in deionized water to prepare a mixed salt solution with a total molar concentration of metal ions of 1.8 mol / L; sodium hydroxide was dissolved in deionized water to prepare OH - An alkaline solution with a molar concentration of 7 mol / L; an ammonia solution with a NH3 mass fraction of 20% is prepared as an ammonia complexing solution;

[0143] b. Add deionized water accounting for 50% of the effective volume of the primary reactor, and then add the alkaline solution and ammonia complex solution prepared in step a as the reaction base solution, so that the NH3 concentration in the primary reactor is 4.5 g / L and the pH value is 11.4;

[0144] c. Under a nitrogen atmosphere and a stirring condition of 350 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the primary reactor in step b. When the primary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the primary reactor, and the clear liquid is discharged into the waste liquid tank. When the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is 3 times the effective volume of the primary reactor, the feeding is stopped, and the materials in the primary reactor are transferred to the secondary reactor;

[0145] The effective volume of the secondary reactor is three times that of the primary reactor. The reaction temperature in the primary reactor is 60°C. Before the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 11.4 and the NH3 concentration at 4.5 g / L. After the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 10.8 and the NH3 concentration at 3.5 g / L.

[0146] d. Under a nitrogen atmosphere and a stirring condition of 300 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the secondary reactor in step c. When the secondary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the secondary reactor, and the clear solution is discharged into the waste liquid tank until the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is twice the effective volume of the secondary reactor, then the feeding is stopped, and the materials in the secondary reactor are transferred to the tertiary reactor;

[0147] The effective volume of the tertiary reactor is twice that of the secondary reactor. The reaction temperature in the secondary reactor is 60°C. The flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the secondary reactor at 10.8 and the NH3 concentration at 3g / L.

[0148] e. Under a nitrogen atmosphere and a stirring condition of 200 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the tertiary reactor in step d. When the tertiary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the tertiary reactor, and the clear solution is discharged into the waste liquid tank. When the D50 particle size of the particles in the tertiary reactor reaches 9 μm, the feeding is stopped;

[0149] The reaction temperature in the third-stage reactor was 60°C, and the flow rates of the alkaline solution and the ammonia complex solution were controlled to maintain the pH value in the third-stage reactor at 10.8 and the NH3 concentration at 3 g / L;

[0150] The oxygen content in the first-stage reactor, the second-stage reactor and the third-stage reactor is less than 0.01% by volume;

[0151] f. After the feeding is stopped in step e, the materials in the three-stage reactor are sequentially washed with water, alkali washed, and washed with water until the pH of the washing liquid is ≤8.0, wherein the alkali solution used for alkali washing is a sodium hydroxide solution with a mass percentage concentration of 1%, and the alkali washing time is 1h;

[0152] g. Put the washed material in step f into an oven, dry it at 120° C. for 10 h, and then pass it through a 200-mesh sieve to obtain a ternary precursor of lithium nickel cobalt manganese oxide (Ni 0.9 Co 0.05 Mn 0.05 (OH)2);

[0153] (2) dissolving cobalt chloride calculated as Co element and aluminum chloride calculated as Al element in a molar ratio of 2:1 in deionized water to prepare a first solution with a total metal ion concentration of 0.5 mol / L;

[0154] Prepare an alkaline solution with a sodium hydroxide concentration of 1.0 mol / L and a sodium carbonate concentration of 0.5 mol / L;

[0155] The first solution and the alkaline solution were added into a colloid mill at a volume ratio of 1:1 and mixed for 3 minutes at a speed of 3000 r / min to obtain cobalt aluminum hydrotalcite Co4Al2(OH) 12 CO3·6H2O suspension;

[0156] The NCM811 precursor, the suspension containing cobalt aluminum hydrotalcite (in terms of solid phase), and nano niobium pentoxide (average particle size of 50 nm) were weighed and mixed in a molar ratio of 100:1:1, stirred and aged in a 98°C water bath for 3 hours, and then washed and filtered repeatedly until the pH of the filtrate was below 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain a pre-product;

[0157] (3) According to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.05, the above pre-product and micro powder lithium hydroxide (average particle size of 7 μm) were weighed and ball milled for 2.5 h, and then heated to 350°C at a temperature rate of 4°C / min in an oxygen atmosphere, and calcined at a constant temperature for 3 h, and then heated to 500°C at a temperature rate of 4°C / min, and calcined at a constant temperature for 3 h, and then heated to 720°C at a temperature rate of 4°C / min, and calcined at a constant temperature for 15 h, and finally cooled to 350°C at a temperature rate of 2°C / min, and then cooled to room temperature with the furnace to obtain niobium-doped nickel cobalt manganese aluminum lithium quaternary material A2, the chemical formula of which is LiNi 0.833 Co 0.083 Mn 0.046 Al 0.01 9Nb 0.019 O2, parameters are listed in Table 1.

[0158] Example 3

[0159] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material A3 was prepared by the method of Example 1, except that:

[0160] (2) dissolving nickel sulfate calculated as Ni element and aluminum sulfate calculated as Al element in a molar ratio of 3:1 in deionized water to prepare a first solution with a total metal ion concentration of 1.0 mol / L;

[0161] Prepare an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L;

[0162] The first solution and the alkaline solution were added into a colloid mill at a volume ratio of 1:1 and mixed for 3 minutes at a speed of 3000 r / min to obtain nickel aluminum hydrotalcite Ni6Al2(OH) 16 CO3·6H2O suspension;

[0163] The NCM811 precursor, the suspension containing nickel aluminum hydrotalcite (in terms of solid phase), and nano niobium pentoxide (average particle size of 50 nm) were weighed and mixed in a molar ratio of 100:1:0.5, stirred and aged in a 98°C water bath for 3 hours, and then washed and filtered repeatedly until the pH of the filtrate was below 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain a pre-product;

[0164] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material A3 was obtained, with the chemical formula LiNi 0.789 Co 0.092 Mn 0.092 Al 0.018 Nb 0.009 O2, parameters are listed in Table 1.

[0165] Comparative Example 1

[0166] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D1 was prepared by the method of Example 1, except that:

[0167] In step (1) b, the NH3 concentration in the primary reactor is 3 g / L and the pH value is 11.0;

[0168] In step (1) c, before the concentration treatment is started, the pH value in the primary reactor is 11.0 and the NH3 concentration is 3 g / L; after the concentration treatment is started, the pH value in the primary reactor is 10.6 and the NH3 concentration is 3 g / L;

[0169] In step (1) d, the pH value in the secondary reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0170] In step (1) e, the pH value in the third-stage reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0171] Finally, the niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D1 was obtained, with the chemical formula LiNi 0.734 Co 0.147 Mn 0.092 Al 0.018 Nb 0.009 O2, parameters are listed in Table 1.

[0172] Comparative Example 2

[0173] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D2 was prepared by the method of Example 2, except that:

[0174] In step (1) b, the NH3 concentration in the primary reactor is 4 g / L and the pH value is 11.3;

[0175] In step (1) c, before the concentration treatment is started, the pH value in the primary reactor is 11.2 and the NH3 concentration is 3.5 g / L; after the concentration treatment is started, the pH value in the primary reactor is 10.5 and the NH3 concentration is 2.6 g / L;

[0176] In step (1) d, the pH value in the secondary reactor is 10.5 and the NH3 concentration is 2.6 g / L;

[0177] In step (1) e, the pH value in the third-stage reactor is 10.5 and the NH3 concentration is 2.6 g / L;

[0178] Finally, the niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D2 was obtained, with the chemical formula LiNi 0.833 Co 0.083 Mn 0.046 Al 0.019 Nb 0.019O2, parameters are listed in Table 1.

[0179] Comparative Example 3

[0180] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D3 was prepared by the method of Example 1, except that:

[0181] In step (1) b, the pH value in the primary reactor is 11.0;

[0182] The chemical formula of niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D3 is LiNi 0.734 Co 0.147 Mn 0.092 Al 0.018 Nb 0.00 9O2, the parameters are listed in Table 1.

[0183] Comparative Example 4

[0184] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D4 was prepared by the method of Example 1, except that:

[0185] In step (1) c, before starting the concentration treatment, the NH3 concentration in the primary reactor is 3.0 g / L;

[0186] The chemical formula of niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D4 is LiNi 0.734 Co 0.147 Mn 0.092 Al 0.018 Nb 0.00 9O2, the parameters are listed in Table 1.

[0187] Comparative Example 5

[0188] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D5 was prepared by the method of Example 3, except that:

[0189] In step (1) b, the NH3 concentration in the primary reactor is 3 g / L and the pH value is 11.0;

[0190] In step (1) c, before the concentration treatment is started, the pH value in the primary reactor is 11.0 and the NH3 concentration is 3 g / L; after the concentration treatment is started, the pH value in the primary reactor is 10.6 and the NH3 concentration is 3 g / L;

[0191] In step (1) d, the pH value in the secondary reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0192] In step (1) e, the pH value in the third-stage reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0193] The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material D5 was obtained, with the chemical formula LiNi 0.789 Co 0.092 Mn 0.092 Al 0.018 Nb 0.009 O2, parameters are listed in Table 1.

[0194] Comparative Example 6

[0195] The niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material D6 was prepared by the method of Example 1, except that commercially available Ni 0.8 Co 0.1 Mn 0.1 (OH)2 ternary precursor is used as nickel-cobalt-manganese precursor, and the chemical formula of quaternary material D6 is LiNi 0.734 Co 0.147 Mn 0.092 Al 0.018 Nb 0.009 O2, parameters are listed in Table 1;

[0196] The quaternary material D6 was tested by scanning electron microscope, and the results are as follows Figure 2 As shown;

[0197] according to Figure 2 It can be seen that the commercially available Ni 0.8 Co 0.1 Mn 0.1 The quaternary material prepared by using the (OH)2 ternary precursor as a nickel-cobalt-manganese precursor has no primary particle core, that is, no core-shell structure.

[0198] Comparative Example 7

[0199] The quaternary material D7 was prepared by the method of Example 1, except that:

[0200] In step (2), no nano niobium pentoxide is added. Finally, an equal molar amount of niobium pentoxide and the lithium nickel-cobalt-manganese-aluminate quaternary material prepared in step (3) are weighed and solid-phase ball milled for 2.5 h, and calcined at 750° C. for 5 h in an oxygen atmosphere. The chemical formula of the quaternary material D7 is LiNi 0.734 Co 0.147 Mn 0.092 Al 0.018 Nb 0.009 O2, parameters are listed in Table 1.

[0201] Table 1

[0202] Example / Comparative Example <![CDATA[A Nb With D Nb Ratio of]]> Span Example 1 1.016 0.664 Example 2 1.009 0.650 Example 3 1.025 0.675 Comparative Example 1 1.022 0.686 Comparative Example 2 1.043 0.684 Comparative Example 3 1.020 0.690 Comparative Example 4 1.018 0.693 Comparative Example 5 1.014 0.688 Comparative Example 6 1.073 1.380 Comparative Example 7 1.946 0.77

[0203] As can be seen from Table 1, according to the comparison between Examples 1-3 and Comparative Example 7, the proportion of Nb element in the surface layer and the bulk phase of the niobium-doped lithium nickel-cobalt-manganese-aluminate quaternary material prepared by the method disclosed in the present invention is basically the same, indicating that the method disclosed in the present invention can prepare a lithium nickel-cobalt-manganese-aluminate quaternary material with uniform Nb element distribution. At the same time, the niobium-doped lithium nickel-cobalt-manganese-aluminate quaternary materials A1-A3 prepared by the method disclosed in the present invention have a smaller diameter than that of Comparative Examples D1-D7, and the particle size distribution is more concentrated.

[0204] according to Figure 1 and Figure 2 In comparison, A1 prepared by the method disclosed in the present invention has a core-shell structure with obvious differences in internal and external appearance, while D6 prepared using commercially available precursors has an ordinary scattered profile without a core-shell structure.

[0205] Test Example 1-10

[0206] The quaternary materials of Examples 1-3 and Comparative Examples 1-7 were used as positive electrode materials, mixed with acetylene black conductive agent and polyvinylidene fluoride binder in a mass ratio of 94:3:3, coated on the surface of aluminum foil current collector, dried at 110°C and pressed into sheets, and electrode sheets with a diameter of 1 cm were obtained by a punching machine. The sheets were vacuum dried in a vacuum oven at 120°C for 24 h as positive electrodes, metal lithium sheets were used as negative electrodes, polyethylene films were used as separators, 1 mol / L LiPF6 / (ethylene carbonate + dimethyl carbonate) was used as electrolyte, wherein the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1, and button batteries were assembled in a glove box.

[0207] The Wuhan Blue Electric CT2001A battery tester was used to test the electrochemical performance, and the charge and discharge voltage range was 2.7-4.3V (vs.Li + / Li). After 5 cycles of charge and discharge at 0.1C, 3 cycles of charge and discharge at 0.2C were performed, and finally a long-term cycle at 0.5C was performed. The results are listed in Table 2.

[0208] Table 2

[0209]

[0210]

[0211] According to the data in Tables 1 and 2, the niobium-doped nickel-cobalt-manganese-aluminum lithium oxide A1-A3 materials prepared by the method disclosed in the present invention have better capacity retention rates after 200 cycles than D1-D7, indicating that the niobium-doped nickel-cobalt-manganese-aluminum lithium oxide quaternary materials prepared by the method disclosed in the present invention have better electrochemical properties.

[0212] Specifically, according to the data comparison of materials A1-A3 and D6, the niobium-doped nickel cobalt manganese aluminum oxide prepared from the nickel-cobalt-manganese ternary precursor prepared by the specific method of the present invention has a core-shell structure, and the capacity retention rate and first discharge capacity of the material are significantly better than those of the material prepared by the commercially available precursor; according to the comparison of A1-A3 and D1-D5, the material prepared by the method of the present invention has a concentrated particle size distribution, and the migration path and deintercalation degree of lithium ions of the material with more uniform particle size during long-term cycling are also more consistent, which is more conducive to maintaining a lower capacity loss and further improving the cycle stability of the material.

[0213] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0214] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0215] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material, characterized in that: The method comprises the following steps: (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to react and obtain a pre-product; (2) ball milling the pre-product and the lithium-containing compound, and heat treating the obtained mixture in an oxygen-containing atmosphere; The aluminum-based hydrotalcite contains a transition metal element, the transition metal element is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1; The method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps: S01. Adding a reaction base liquid to a primary reactor, wherein the reaction base liquid comprises water, an alkaline solution and an ammonia complexing liquid, and the amount of the reaction base liquid added is 30%-80% of the effective volume of the primary reactor; S02. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the primary reactor, and when the primary reactor is full, the material in the primary reactor is concentrated, and the concentrated solution is refluxed into the primary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 3-4 times the effective volume of the primary reactor, and the material in the primary reactor is transferred to the secondary reactor; S03. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the secondary reactor, and when the secondary reactor is full, the material in the secondary reactor is concentrated, and the concentrated solution is refluxed into the secondary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 2-3 times the effective volume of the secondary reactor, and the material in the secondary reactor is transferred into the tertiary reactor; S04. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, the alkaline solution and the ammonia complex solution are continuously introduced into the tertiary reactor, and when the tertiary reactor is full, the material in the tertiary reactor is concentrated, and the concentrated solution is refluxed into the tertiary reactor until the D50 particle size of the particles in the tertiary reactor is 9-11 μm; In step S01, when adding the reaction base solution, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-5 g / L; In step S02, before the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-4.5 g / L; after the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 10.7-11.0 and the NH3 concentration is 3-4 g / L; In step S03, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the secondary reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L; In step S04, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the three-stage reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L.

2. The method according to claim 1, wherein: The chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2, where 0 <a≤0.1,0<b≤0.1。 3. The method according to claim 1, wherein: In step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite to the niobium element in the niobium-containing compound is 2:1 or more.

4. The method according to claim 1, wherein: The niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate; The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate; Optionally, the average particle size of the niobium-containing compound is 50-80 nm, and the average particle size of the lithium-containing compound is 6-8 μm.

5. The method according to claim 1, wherein: The molar ratio of the total molar sum of nickel element, cobalt element, manganese element, aluminum element and niobium element in the pre-product to the molar ratio of the lithium element in the lithium-containing compound is 1:(1.0-1.1).

6. The method according to claim 1, wherein: In step (2), the heat treatment comprises the following steps: a. Raise the temperature to 300-400°C at a heating rate of 1-8°C / min for the first calcination for 1-3h; b. Continue heating to 450-500°C at a heating rate of 1-8°C / min and perform a second calcination for 1-3h; c. Continue heating to 700-800°C at a heating rate of 2-6°C / min for the third calcination for 10-15h; d. Cool down to 300-400°C at a cooling rate of 1-3°C / min, and then cool to below 100°C; The oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere.

7. The method according to claim 1, wherein: The ball milling time is 1-4h.

8. The method according to claim 1, wherein: The mixed salt solution contains nickel ions, cobalt ions and manganese ions, and the total molar concentration of the nickel ions, the cobalt ions and the manganese ions is 1.8-2.5 mol / L.

9. The method according to claim 1, wherein: The alkaline solution comprises a sodium hydroxide solution and / or a potassium hydroxide solution. - The concentration is 5-10 mol / L; The ammonia complex solution includes aqueous ammonia, and the mass fraction of NH3 in the ammonia complex solution is 15-22%.

10. The method according to claim 1, wherein: In the primary reactor, the secondary reactor and the tertiary reactor, the reaction temperature is 50-65° C., the stirring speed is 100-400 rpm, and the oxygen content is less than 0.01% by volume.

11. The method according to claim 1, wherein: The effective volume of the secondary reactor is 3-4 times that of the primary reactor, and the effective volume of the tertiary reactor is 3-4 times that of the secondary reactor.

12. Niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material prepared by the method according to any one of claims 1 to 11.

13. The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material according to claim 12, wherein: The quaternary material is a particle including a core and a shell layer coated outside the core; The diameter distance of the particles is less than 0.

68.

14. The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material according to claim 12, wherein: A Nb With D Nb The ratio is 0.9-1.1; Based on the total molar amount of nickel, cobalt, manganese, aluminum and niobium on the surface of the particles, A Nb represents the molar percentage of niobium element on the surface of the particle; Based on the total molar mass of nickel, cobalt, manganese, aluminum and niobium in the bulk phase of the particles, D Nb represents the molar ratio of niobium element in the bulk phase of the particles.

15. The niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material according to claim 12, wherein: The quaternary material includes a chemical formula of LiNi 1-x-y-z-n Co x Mn y Al z Nb n Particles of O2, 0<x<0.2, 0<y<0.1, 0<z<0.05, 0.002<n<0.

02.

16. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the niobium-doped lithium nickel-cobalt-manganese-aluminum oxide quaternary material according to any one of claims 12 to 15.